Synthesis and Characterisation of Graphene Oxide Catalysts for Glycerol Acetylation - Hidayati, Nur; Khoiruddin, Wahib; Purnama, Herry; Effendy, Marwan (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Glycerol in large quantities as a by-product of biodiesel production is a promising feedstock to be converted into more valuable products such as acetin. In this work, acetin converted from glycerol acetylation with acetic acid was performed over graphene oxide as a catalyst in a batch reactor. The study's objective was to evaluate the effect of sodium nitrate amount in the catalyst preparation on the catalyst's characteristics and catalytic performance. The graphene oxide (GO) catalysts were characterised by various tests, such as SEM-EDX for their morphology, the nitrogen adsorption capacity using Breneur-Emmet Teller (BET), structural analysis using XRD, functional group using FTIR, and catalytic activity on glycerol acetylation. The GO1, GO2, and GO3 catalysts were varied based on the NaNO3 amount in the modified Hummer method. The experiments found that the NaNO3 amount in catalyst preparation plays a vital role in GO structure formation. The GO2 catalyst has the highest performance, as indicated by the highest surface area, pore volume, and size. High glycerol conversion (94 %) and selectivity toward the interest products of triacetin (24 %) and diacetin + triacetin (83 %) were reached in 2 h of reaction using three wt.% catalysts, 110 °C reaction temperature, and 1:9 molar ratio of glycerol to acetic acid. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).